2015
DOI: 10.1093/molbev/msv210
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of DNA-Binding Sites of a Floral Master Regulatory Transcription Factor

Abstract: Flower development is controlled by the action of key regulatory transcription factors of the MADS-domain family. The function of these factors appears to be highly conserved among species based on mutant phenotypes. However, the conservation of their downstream processes is much less well understood, mostly because the evolutionary turnover and variation of their DNA-binding sites (BSs) among plant species have not yet been experimentally determined. Here, we performed comparative ChIP (chromatin immunoprecip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 67 publications
3
37
1
Order By: Relevance
“…The relationship among these promoters is typical of a subdivision into evolutionary lineages previously reported for the WOX proteins in grapevine and other species: a modern clade (WUS, WOX1, 2, 3, 4, 5, 6, and 7) separated from an intermediate clade (WOX8, 9, 11, and 12) and an ancient clade (WOX10, 13, and 14)82034. These results showed that the evolutionary relations among different WOX proteins can also be conserved in promoter sequences, suggesting a parallel evolution between coding sequences and gene regulation35.…”
Section: Resultsmentioning
confidence: 76%
“…The relationship among these promoters is typical of a subdivision into evolutionary lineages previously reported for the WOX proteins in grapevine and other species: a modern clade (WUS, WOX1, 2, 3, 4, 5, 6, and 7) separated from an intermediate clade (WOX8, 9, 11, and 12) and an ancient clade (WOX10, 13, and 14)82034. These results showed that the evolutionary relations among different WOX proteins can also be conserved in promoter sequences, suggesting a parallel evolution between coding sequences and gene regulation35.…”
Section: Resultsmentioning
confidence: 76%
“…The previously defined binding site for DREB/CBF transcription factors, which are induced in response to drought and cold stress (Muiño et al, 2016), showed significant enrichment in the proximal promoters of gene pairs in the DE2 category, as well as significant purification in the proximal promoters of gene pairs in the DE0 category (Supplemental Figure 5). As transcription factors are often associated with larger quantities of conserved noncoding sequences (CNSs) (Freeling et al, 2007;Turco et al, 2013), we also investigated the number and quantity of conserved noncoding sequence associated with different classes of genes; however, no strong patterns were observed ( Figure 6D).…”
Section: Functional Differences Between Genes With Conserved or Lineamentioning
confidence: 87%
“…These genes could provide the information necessary for establishing the basic blueprint for the different types of floral organs. While such studies have not yet been conducted systematically, the first steps in this direction have already been taken (Muiño et al, 2016) and will likely lead to much activity in this area in years to come.…”
Section: Floral Organ Specificationmentioning
confidence: 99%